Viroids as a tool to study RNA-directed DNA methylation in plants - Wassenegger, Michael; Dalakouras, Athanasios (Cells, 2021)
Viroids are plant pathogenic, circular, non-coding, single-stranded RNAs (ssRNAs). Members of the Pospiviroidae family replicate in the nucleus of plant cells through double-stranded RNA (dsRNA) intermediates, thus triggering the host’s RNA interference (RNAi) machinery. In plants, the two RNAi pillars are Post-Transcriptional Gene Silencing (PTGS) and RNA-directed DNA Methylation (RdDM), and the latter has the potential to trigger Transcriptional Gene Silencing (TGS). Over the last three decades, the employment of viroid-based systems has immensely contributed to our understanding of both of these RNAi facets. In this review, we highlight the role of Pospiviroidae in the discovery of RdDM, expound the gradual elucidation through the years of the diverse array of RdDM’s mechanistic details and propose a revised RdDM model based on the cumulative amount of evidence from viroid and non-viroid systems.
Gesehen am 16.06.2021